Development of New Business Opportunities for Sustainable Development – Lesson Learned from Pandemic Crisis - ȘERBAN, Octavian; VÎLCU (TĂNASE), Elena Crizantema; SABIE, Oana Matilda; DUMITRACHE, Victor Marian (European Journal of Sustainable Development, 2023)
During the pandemic crisis it was observed that the whole global economy was affected especially by severe disruption of supply-demand balance. Even so, the most affected were low-income economies because of lack of resources to redistribute in the sake of resilience and recovery. We cannot say that the developed economies were not affected, in real terms probably much more than the lower-income ones, but developed countries or regions were capable to dislocate huge financial support to overcome the crisis and to quickly regain the level before shock. The purpose of this research is to analyse the effects of health crisis over the economy. Because four crises are overlapping (health, energy, geostrategic conflict, and food), it is quite difficult to measure the impact of each driver with accuracy. To determine the impact of those four factors is necessary to understand the dynamic of productivity and competitiveness during shocks, even though we cope with health influence, energy prices, geopolitical turbulence, or food security. All in all, partially for energy crisis, the other crises were totally unexpected, and the response of humanity, global institutions, alliances, and association of countries is customized according to the evolution of turbulences. Here is the role of government because, from the capacity building perspective, there is necessary more integration between government, research/education, and business ecosystem in order to encourage innovation, creativity, and entrepreneurship. In the 4th Industrial Revolution, the main resource and key factor is knowledge embedded in every step of the process, embodied in equipment and machinery, on the one hand, and in human, on the other hand. Robotics, new materials, nanotechnologies, and digital environment give a new dimension to productivity and competitiveness. From this perspective, our goal is to demonstrate de supremacy of collaborative approach for shaping knowledge in the way of creativity, innovation, entrepreneurship, productivity, and competitiveness. Keywords: productivity, competitiveness, crisis, sustainable development, knowledge economy